2005
DOI: 10.1071/rj05012
|View full text |Cite
|
Sign up to set email alerts
|

Pasture production in cleared and uncleared grazing systems of central Queensland, Australia

Abstract: Abstract. Clearing land of trees and introducing exotic pastures to enhance pasture and cattle production and hence enterprise financial performance are widely practised in Queensland. The results from many previous studies on tree clearing have emphasised the gains in pasture production, but over periods of less than 10-15 years after clearing. The present study questioned the sustainability of pasture production in cleared systems over a longer time-frame (>10 years of clearing). For this, three different ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Our results imply that the introduction and spread of buffel grass is associated with a substantial change in bird species composition, but the process and closer delineation of this change may need further, more tightly focused research; and the interpretation of our results is hampered by the lack of such previous investigation of the consequences to birds of buffel grass invasion, and perhaps by associations between buffel grass establishment and other environmental variation. Nonetheless, previous studies have demonstrated that buffel grass may have a major impact on floristic diversity (Fairfax & Fensham 2000; Franks 2002; Jackson 2005; Kaur et al . 2005) and on fire intensity (Butler & Fairfax 2003; Clarke et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results imply that the introduction and spread of buffel grass is associated with a substantial change in bird species composition, but the process and closer delineation of this change may need further, more tightly focused research; and the interpretation of our results is hampered by the lack of such previous investigation of the consequences to birds of buffel grass invasion, and perhaps by associations between buffel grass establishment and other environmental variation. Nonetheless, previous studies have demonstrated that buffel grass may have a major impact on floristic diversity (Fairfax & Fensham 2000; Franks 2002; Jackson 2005; Kaur et al . 2005) and on fire intensity (Butler & Fairfax 2003; Clarke et al .…”
Section: Discussionmentioning
confidence: 99%
“…But vegetation clearance is but part of a more complex disturbance regime in this region. Cleared areas have usually been sown with exotic pasture, particularly buffel grass Cenchrus ciliaris , which allows an increased grazing intensity, at least in the short term (Kaur et al . 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to altered N and C relations, we found that P contents of grasses were elevated at cleared sites, which is a potential cause for increased pasture production at least in the short to medium term after clearing (Scanlan 2002;Kaur et al 2005). Causes for improved P nutrition of grasses at cleared sites include reduced competition from woody species, but how well native and exotic grasses acquire P depends on species' abilities as well as soil properties.…”
Section: Discussionmentioning
confidence: 86%
“…There is evidence that removal of trees from these savannas increases pasture production in the short-term (<10 years) (Scanlan 2002), but long-term consequences of clearing are largely unknown (Schmidt and Lamble 2002). In semi-arid Eucalyptus savanna and Acacia woodland, pasture production decreased significantly in the long term (~30 years) (Kaur et al 2005).…”
Section: Introductionmentioning
confidence: 98%
“…The failure of perennial grasses to recover even decades after disturbance [19] suggests that shrub removal is ineffective in the long-term. Though shrub removal might increase pasture production in the short-term (<10 years [20]), long-term studies (~30 years) suggest otherwise [21]. The imposition of grazing shortly after ploughing might retard the recovery of these systems and deplete grass soil seedbanks.…”
Section: Ploughing May Lead To Monospecific Shrub Standsmentioning
confidence: 99%